LAFIAL: Pandemi COVID-19 Sebagai Momentum Kemandirian Industri Farmasi Menuju Ketahanan Kesehatan Nasional - Ruskar, Dandung; Hastuti, Septianita; Wahyudi, Heri; Dewa Ketut Kerta Widana, I; Khoirudin Apriyadi, Rio (PENDIPA Journal of Science Education, 2021)
[LAFIAL: COVID-19 Pandemic As The Pharmaceutical Industry’s Independence Momentum Towards National Health Resilience] Ninety percent of the distribution of medicinal raw materials and medical devices of the domestic pharmaceutical industry is sourced from imports from other countries. One of the exporter countries is China which still feels it has sovereignty over part of the North Natuna Sea (LNU) in the South China Sea conflict (LCS). In the conflict, Indonesia vehemently denies any unilateral claims from China. This has the potential to stop import access to Indonesia which ultimately has an impact on the development of the domestic pharmaceutical industry. In Presidential Instruction No. 6 of 2016, the government wants the realization of the resilience of the domestic pharmaceutical industry. Industrial resilience in the pharmaceutical sector has multi-benefits including accelerating national economic growth, meeting the scarcity of pharmaceutical products and medical devices as a result of COVID-19, and at the same time reducing import dependence on medicinal raw materials and medical devices. Navy Pharmaceutical Institute (LAFIAL) as the military pharmaceutical industry has a strategic capacity and role against both military and nonmilitary threats that can harm the health of the people of Indonesia. The involvement of LAFIAL is expected to further encourage and strengthen the independence of the pharmaceutical industry. This article is qualitative research through a descriptive approach with an analysis of studies from several references to describe the current pharmaceutical industry profile and the COVID-19 pandemic impact affecting the pharmaceutical industry independence, coupled with interviews from several sources. The interview results provide an overview of how the LAFIAL benefits as a military pharmaceutical industry to support health defense, especially during the COVID-19 pandemic.